Impact of Shoes Brand Preference on Customer Satisfaction - Goet, Joginder; Kharel, Kiran (KIC International Journal of Social Science and Management, 2023)
In a competitive business environment, concerns like customer satisfaction and brand preferences are becoming very important to corporate operations. The core objective of this research was to look at the influence of factors of brand preference on Customer Satisfaction with shoes. Primary data were employed in the research. Correlation and regression were utilized to calculate, analyze, and interpret the data for the descriptive and causal-comparative research design. The entire population is used in the study as shoe users. The population was represented by a sample of 390 respondents. A convenience sampling method was used to determine the sample size. According to the findings, brand preference factors such as Product Quality (PQ), Design (DG), Store Environment (SE), Service Quality (SQ), Promotion (PR), and Brand Image (BI) have a considerable impact on Customer Satisfaction in the Kathmandu Valley. But one factor, Brand Name (BN) has no considerable impact on Customer Satisfaction. The outcomes of this study show the significant link between factors of brand preference and Customer Satisfaction in the Kathmandu Valley. The Pearson coefficient between Brand Name (BN), Product Quality (PQ), Design (DG), Store Environment (SE), Service Quality (SQ), Promotion (PR), and Brand Image (BI) has been determined to be positive by correlation analysis.Because the value of significance was less than 0.05, all alternative hypotheses were accepted. As a result, we may deduce that the interactions positively impact Customer Satisfaction. Brand preference factors except for Brand Name (BN) have a significant influence on Customer Satisfaction.